The environment in the public sphere : democracy and discourse in the genetically modified organism debate in Ireland - Motherway, Brian (Trinity College (Dublin, Ireland). Department of Sociology, 2002)
This thesis is an exploration of the possibilities of democratising environmental decision-making in Ireland. A specific attempt at enhancing dem ocratic involvement in policy decision-making is analysed. The case study for this analysis is the debate over genetically modified crops and foods.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin